Faktor - Faktor Yang Berhubungan Dengan Kejadian Diare Dalam Pemberian Mpasi Bayi 6-12 Bulan Di Puskemas Sawah Lebar Tahun 2024 - Koryani, Ikke Agustin; Rahmawati, Diyah Tepi; Putri, Yesi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Data from UNICEF (2020), explains that every year the death rate among children reaches 91,000 with the main cause being preventable infections. One of these infectious diseases is diarrhea or in the medical world it is called gastroenteritis. The aim of the research is to determine the factors associated with the incidence of diarrhea in giving MPASI to babies 6-12 months at the Sawah Lebar Community Health Center in 2024. The method used in this research uses analytical research with a cross sectional design. The population of this study included 375 babies in the working area of ​​the Sawah Lebar Community Health Center. The sampling technique used the Accidental Sampling technique based on inclusion criteria. The sample used was 79 people. The bivariate test results show that the variable maternal knowledge with the incidence of diarrhea obtained a chi-square p-value of 0.001, the history of exclusive breastfeeding with the incidence of diarrhea obtained a chi-square p-value of 0.001, the method of giving MPASI and the incidence of diarrhea obtained a chi-square p-value. value is 0.001, so it can be concluded that there is a relationship between mother's knowledge, history of exclusive breastfeeding and how to give MPASI with the incidence of diarrhea in giving MPASI to babies 6-12 months at the Sawah Lebar Community Health Center in 2024. It is recommended that the community health center provide information about the importance of knowledge about diarrhea and providing breast milk. Exclusively, always wash your hands with soap so that your baby doesn't experience diarrhea.